The leaders’ role in leading and managing organisational change in higher education institutions - Elni Jeini Usoh; Frandy Efraim Fritz Karundeng (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The survival of an organisation does not only depend on continuous change to encounter the rapid shifting in marketplace and organisational alliances, but also to adjust their operational process. The purpose of this study is to examine the role of the leader in the process of leading and managing organisational change, with some parts focused on higher education institutions. This study utilized research literature review to support author’s notions and arguments. The research result found that the critical function of higher education institutions has been changed to a more pragmatic role, universities have changed their previous role not only to serve society, but also more focus on supporting the economy and promoting the quality of life of its citizens. The main role of the higher institution leader in this situation is as mediator between policy and practice. In conclusion, organisational change is an inevitable process in contemporary organisations, including higher education institutions. The key findings suggest that the leaders should create and share vision, develop a strong partnership from those who can contribute to change, improve competence, and reinforce new structure and culture which appropriate to the new environment, by encouraging motivation, communication, participation, empowerment and commitment.